Rumen degradability characteristics of normal maize stover and silage, and quality protein maize silage-based diets offered to cows - Tamir, B.; Gebrehawariat, E.; Tegegne, Azage; Kortu, M.Y. (Springer, 2012)
Rumen degradability characteristics of dry matter (DM), organic matter (OM) and crude protein (CP) of normal maize (NM) stover (T1)-, NM silage (T2)- and quality protein maize (QPM) silage (T3)-based diets were studied using three rumen-fistulated Boran × Friesian non-lactating cows (371 ± 32.00 kg) in 3 × 3 Latin Square Design. Cows were supplemented with a similar concentrate mix. In sacco degradability of DM and OM indicated that the (a) values of DM (128) and OM (114) for NM stover were lower (P < 0.001) than that for NM silage (268 and 253) and for QPM silage (323 and 303), respectively. The (a) value for CP was lower (P < 0.05) for QPM silage (286) than for NM stover (404) and NM silage (326). The (b) values of DM in NM stover (597) and NM silage (535) were higher (P < 0.05) than in QPM silage (499). The (b) value of CP in NM stover (372) was lower (P < 0.05) than in NM silage (655) and in QPM silage (608). Rate of degradation of OM in NM stover and NM silage, each with 0.03, was faster (P < 0.01) than in QPM silage (0.02). Moreover, QPM silage had higher potentially degradable fraction for DM (821) (P < 0.05) and OM (840) (P < 0.01) than DM (725) and OM (712) in NM stover. The mean rumen ammonia concentration (209 mg/l) of QPM silage was higher (P < 0.05) than that of NM stover (179 mg/l) and NM silage (170 mg/l). The average rumen pH (6.1) in cows fed QPM silage was lowest (P < 0.05) compared to pH (6.3) in cows fed either NM stover or silage. The concentration of total volatile fatty acids (116 mmol/l) in the rumen of cows incubated with QPM silage was higher (P < 0.001) than in those incubated with NM stover (113 mmol/l) and NM silage (110 mmol/l). It was concluded that QPM silage-based diet was superior in DM and OM degradability, and had higher ammonia and VFA concentration than NM stover-based diet. No differences have been observed in all parameters measured between QPM and NM silages.